Technology and Firm Performance in Mexico - López-Acevedo, Gladys (World Bank, Washington, DC, 2013)
The author investigates the relationship between a firm's adoption of new manufacturing technology and its performance. A panel database that identifies technological adoption and tracks firms over time allows the use of different measures of firm performance-wages, productivity, net employment growth, job creation, and job destruction. Results show that technology is associated with high firm performance in all these metrics. The effect of new technology on performance is larger for firms located in the north and in Mexico City. This marginal value significantly increased after the 1994 crisis and the North American Free Trade Agreement. Furthermore, technology increased the wage of semi-skilled workers compared with unskilled workers by about 11 percent over seven years.